Life away from home an exploration of the experiences of yolanda environmental migrants in Rosario, Cavite. - Tolentino, Rexter Day M. (2016.)
Through Interpretative Phenomenological Analysis (IPA), I examined the lived experiences of the environmental migrants of typhoon Yolanda residing in Rosario, Cavite. I particularly focused on the accounts of survivors living in La Isla Bonita de Salinas who relocated due to the typhoon. Based on nine unstructured in-depth interviews, results show that the migrants expressed various reactions to the disaster, and faced challenges and changes to their lives after relocating. Despite these circumstances, some found contentment in their new life. However, the migrants still found it difficult to choose between going back to Leyte or staying in the site even after several years. In general, life as environmental migrants depended on two interacting dimensions based on the participants? contentment and displeasure on the conditions present in the relocation site. These affected the way they viewed their new life and the extent of the government?s assistance. These finding provide great insights to the psychological and social dimensions of the environmental migration phenomenon along with the significance of its discussion in current disaster research which can be used to improve quality of assistance offered to the migrants including the introduction of programs to help in developing social relations within the migrant-rich community.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Environmental migrants -- Typhoon Yolanda -- Rosario, Cavite -- Research